2006
DOI: 10.1097/01.brs.0000240691.35707.e8
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Evaluation of Superior-Segment Facet-Joint Violation After Pedicle Instrumentation of the Lumbar Spine With a Midline Surgical Approach

Abstract: The left side, single-level fusion, and most cephalad pedicle screws at L5 are targets for interventions to reduce pedicle violations in this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 10 publications
1
66
1
Order By: Relevance
“…Fusion procedures have been linked to a variety of negative side effects such as adjacent segment degeneration and instability, superior segment facet joint violation, adjacent segment spondylarthrosis with consecutive spinal canal stenosis as well as persisting pain from harvesting of the autologous bone graft [9,21,23,30,35,49,63]. Previous studies have revealed the facet and iliosacral joints to be a source of post-operative pain in a considerable number of patients [29,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion procedures have been linked to a variety of negative side effects such as adjacent segment degeneration and instability, superior segment facet joint violation, adjacent segment spondylarthrosis with consecutive spinal canal stenosis as well as persisting pain from harvesting of the autologous bone graft [9,21,23,30,35,49,63]. Previous studies have revealed the facet and iliosacral joints to be a source of post-operative pain in a considerable number of patients [29,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Total lumbar disc replacement Fusion of lumbar motion segments has been associated with a variety of early and late complications in a considerable number of patients [1][2][3][4][5][6][7][8][9][10][11][12]. In an attempt to avoid these fusion-related negative side effects, motion preserving technologies such as total lumbar disc replacement (TDR) procedures have been introduced.…”
Section: Ddd Versus Preoperative Clinical Symptomatologymentioning
confidence: 99%
“…However, a variety of negative side effects have been linked with both the posterior approach as well as the fusion of lumbar motion segments. These negative side effects include access-related collateral muscle damage, sagittal imbalance, graft site morbidity, screw loosening, pseudarthrosis, adjacent level facet joint violations in posterior instrumented fusion techniques, high rates of adjacent level pathologies as well as considerable complication and reoperation rates [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%